A Recent Review of Retinopathy of Prematurity : Scenario in South East Asia - Sultana, Zakia; Roy, Subarna; Talukder, Abdul Khaleque (Journal of National Institute of Ophthalmology, 2026)
Retinopathy of prematurity (ROP) is a vasoproliferative ocular condition that appears due to inappropriate vascularization of the immature retina of preterm neonates . If it progresses , it may cause visual morbidity even permanent blindness . South East Asian Countries like Bangladesh, Pakistan, India etc had improved medical services now a days . With modified medical cares and lowing infant mortality rate they are facing new threats like ROP . But it’s very warm and encouraging that these countries are defending with all their resources and engaging more each day to prevent visual morbidity and blindness due to ROP . J.Natl.Inst.Ophthalmol.2024;7(1): 60-67